A Multidimensional Approach to the Management of Severe Asthma: Inflammometry, Molecular Microbiology and Bronchial Thermoplasty. Issue 4 (2015) - Cox, Conor; Kjarsgaard, Melanie; Surette, Michael G; Cox, P Gerard; Nair, Parameswaran
Abstract : The authors illustrate the merits of identifying the components of diseases (eg, bronchitis and airway hyper-responsiveness) that contribute to exacerbations in the management of a patient with severe asthma. Quantitative cell counts in sputum identified a neutrophilic – as opposed to eosinophilic – bronchitis that enabled a stepwise weaning of prednisone. Molecular microbiology and extended culture methods identified anaerobes and other airway microbiome that helped to guide the use of antibiotics. Further control of asthma was achieved by performing bronchial thermoplasty.